PENGARUH DISIPLIN KERJA, PENGEMBANGAN KARIR, DAN TUNJANGAN TERHADAP KINERJA KARYAWAN PLANET SPORT SENAYAN CITY - Edi Siregar; Farla Aulia (Jurnal Manajemen, 2019)
This study aims to determine the effect of work discipline, career development, and allowance variables partially or simultaneously on employee performance. The population or samples in this study were employees of Planet Sport in the South Jakarta area. Data collection used in this study was taken using random sampling. Data collection methods used in this study is observation and questionnaire data, and the type of data used in this study is primary data. In addition there are several methods of data analysis in this study, namely the validity test, reliability test, descriptive analysis, multiple linear regression, classical assumption test and hypothesis testing. Based on predetermined criteria, sample data that has been used is 60 out of a total of 210 questionnaires. From the results of the test simultaneously and partially prove that the variables of work disclipine, career development, and allowance together - the same influence on the performance of employees of the planet sport senayan city